Sonographic Predictors of Thyroid Cancer: A comprehensive Systemic Review and Meta-analysis. - Sarki, Sajid Rasheed; Shahid, Zohaib; Arslan, Syed Asadullah; Khan, Muhammad; Ashraf, Saba; Hussain, Imam; Ahmad Raza, Muhammad; Kaleem Akhter, Muhammad (Journal of Neonatal Surgery, 2025)
Objective: To evaluate Effectiveness of thyroid ultrasound in detecting cancer among nodules with uncertain fine-needle aspiration performed symptomatically for thyroid cancer Material and Method: We included individuals with thyroid nodules with thyroidectomy following ultrasonography (US) examination. In order to ensure precise confirmation of malignancy or benign status, only studies where the surgical specimens were clearly identified by histological analysis were taken into consideration. All relevant studies were obtained in full text for the systematic review and meta-analysis in order to provide a thorough assessment. Stata v11.0 software was used for statistical studies, including pooled estimates and diagnostic performance computations. Results: A total of 12,816 nodules were found in 52 observational investigations. 1852 nodules with unclear cytology were categorized as a separate category in 10 investigations. All US characteristics of nonrandom nodules were significantly associated with cancer, with probabilities ranging from 2.15 to 3.77; microcalcifications, discontinuous edges, and a taller than broad form had favorable probability ratios (LHR; 5.16, 4.19, 10.17) and significant particularities (Sp; 89.8%, 85.3%, and 98.1%). Lack of flexibility was the only factor with superior diagnostic effectiveness (sensitivity 89.1%, Sp 88.3%, and positive LHR 8.19). Conclusion: Malignant thyroid nodules cannot be diagnosed by a single ultrasound feature. Certain sonographic characteristics suggest higher cancer risk, and combined assessment with clinical factors improves patient management. Elastography shows potential but requires further validation